Single Tumor Cells With Epithelial-Like Morphology Are Associated With Breast Cancer Metastasis - Tashireva, Liubov A.; Zavyalova, Marina V.; Savelieva, Olga E.; Gerashchenko, Tatyana S.; Kaigorodova, Evgeniya V.; Denisov, Evgeny V.; Perelmuter, Vladimir M. (Frontiers in Oncology, 2020)
Introduction. The identification of tumor cells that can be potential metastatic seeds would reach two key aims – prognosis of metastasis risk and appointment of the optimal adjuvant therapy to prevent metastatic disease. Single tumor cells (STCs) located out of multicellular structures can most likely demonstrate features that are needed to initiate metastasis. Methods. 135 patients with invasive breast carcinoma of no special type have been enrolled. Molecular subtypes of breast cancer were categorized according to St. Gallen recommendations. Hematoxylin and eosin staining were used to identify STCs with epithelial-like morphology (eSTCs) in breast tumors. Immunofluorescence staining was applied to evaluate stemness and epithelial-mesenchymal transition (EMT) in STCs. Correlation between STCs and recurrence and metastasis-free survival was performed using the Kaplan-Meier method and the log-rank test. Results. Distant metastasis was more frequent in eSTC-positive than eSTC-negative patients (28.0% vs. 9.4%, р=0.007). When tumor types were analyzed separately, distant metastasis tented to be more frequent in eSTC-positive than eSTC-negative patients for HER2-positive cancer (75.0% (3/4) vs. 12.5% (1/8), р=0.066). In luminal A (22.7% (5/22) vs. 10.0% (3/30), р=0.259), luminal B (21.1% (4/19) vs. 6.7% (2/30), р=0.189) and triple-negative (40.0% (2/5) vs. 11.8% (2/17), р=0.209) cancers, distance metastasis was not associated with eSTCs. Median metastasis-free survival (MFS) was not reached in eSTC-positive and eSTC-negative patients eSTC-positive patients had a higher risk of breast cancer metastasis (hazard ratio (HR) 3.57, 95% confidence interval (CI): 1.46-8.71; p=0.001). When tumor types were analyzed separately, a higher risk of breast cancer metastasis had only in HER2-positive patients (HR 8.49, 95% CI: 1.29-55.59; p=0.016). Immunofluorescence analysis revealed mesenchymal-like STCs (mSTCs) and inter- and intratumor heterogeneity in STCs. There were breast tumors with either eSTCs or mSTCs and tumors with both types of STCs. Both eSTCs and mSTCs were represented by cells with different stem and/or EMT phenotypes. Conclusions. STCs with epithelial-like morphology contribute to breast cancer metastasis and represent an attractive model for studying mechanisms of metastatic seeding. The assessment of STCs in histological sections of breast tumors can be a simple and effective method for prediction of metastasis risk.